2020
DOI: 10.1177/1836939120979064
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood educators’ well-being, work environments and ‘quality’: Possibilities for changing policy and practice

Abstract: A child’s right to high quality education not only relies on a competent and skilled workforce, but one in which educators are well. Supporting a well workforce requires governments, organisations and educators to attend to work environment quality. This attention needs be based on sound, relevant evidence. In this paper we contribute evidence of educators’ well-being from the survey component of an Australian study with 73 participants. We map results against international guidelines, and policy openings in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…Similarly to DCA reports, Golebiowska et al (2018) state that overseas-born educators tend to stay in their jobs longer than their Australian-born counterparts. (Gibbs, 2020;Gide, 2017), the wellbeing of the educators (Cumming et al, 2021;Cumming & Wong, 2018), and workforce issues (Irvine et al, 2016;.…”
Section: Cald Workforce In the Context Of Australian Ecementioning
confidence: 99%
See 4 more Smart Citations
“…Similarly to DCA reports, Golebiowska et al (2018) state that overseas-born educators tend to stay in their jobs longer than their Australian-born counterparts. (Gibbs, 2020;Gide, 2017), the wellbeing of the educators (Cumming et al, 2021;Cumming & Wong, 2018), and workforce issues (Irvine et al, 2016;.…”
Section: Cald Workforce In the Context Of Australian Ecementioning
confidence: 99%
“…Additionally, in the most recent study on educator well-being, 24 of the 73 participants were from CALD backgrounds (people who spoke English as well as another language in their daily lives); three participants indicated that their religious background, and two that their cultural background, was not welcomed in their centre. A further 31.5% and 20.5% were ambiguous about the degree to which their religious and cultural identity was welcomed in their centre – respectively (Cumming et al, 2021). Golebiowska et al (2018) used the ABS 2011 census data to explore the impact of overseas-born workers in the Northern Territory ECE workforce.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations